Do Mindfulness‐Based Interventions Reduce Pain Intensity? A Critical Review of the Literature. Issue 2 (13th December 2012) - Reiner, Keren; Tibi, Lee; Lipsitz, Joshua D.
Abstract Background Mindfulness‐based interventions (MBIs) emphasizing a nonjudgmental attitude toward present moment experience are widely used for chronic pain patients. Although changing or controlling pain is not an explicit aim of MBIs, recent experimental studies suggest that mindfulness practice may lead to changes in pain tolerance and pain intensity ratings. Objective The objective of this review is to investigate the specific effect of MBIs on pain intensity. Methods A literature search was conducted using the databases PUBMED and PsycINFO for relevant articles published from 1960 to December 2010. We additionally conducted a manual search of references from the retrieved articles. Only studies providing detailed results on change in pain intensity ratings were included. Results Sixteen studies were included in this review (eight uncontrolled and eight controlled trials). In most studies (10 of 16), there was significantly decreased pain intensity in the MBI group. Findings were more consistently positive for samples limited to clinical pain (9 of 11). In addition, most controlled trials (6 of 8) reveal higher reductions in pain intensity for MBIs compared with control groups. Results from follow‐up assessments reveal that reductions in pain intensity were generally well maintained. Conclusions Findings suggest that MBIs decrease the intensity of pain for chronic pain patients. We discuss implications for understanding mechanisms of change in MBIs.